KERANGKA HUKUM KESEHATAN KERJA DI SEKTOR INFORMAL: KAJIAN KOMPARATIF INDONESIA DAN NEGARA ASEAN - Gunawan Widjaja (CV. Adiba Aisha Amira, 2026)
This study examines the legal framework for occupational health in the informal sector in Indonesia through a comparative analysis with several ASEAN countries. The informal sector is characterised by flexible and dispersed working arrangements and often falls outside the scope of formal labour inspection, leaving workers in this sector vulnerable to workplace accidents and work-related illnesses. In Indonesia, occupational health protection for informal workers is already enshrined in law through the constitution, health legislation, and technical policies such as the Occupational Health Service Posts (Pos UKK). However, its implementation still faces challenges in the form of limited oversight, poor access to services, and weak cross-sectoral integration. Through a comparison with other ASEAN countries, this study demonstrates that protection for informal workers is more effective when supported by an approach that is simple, participatory, community-based and integrated into national policy. The findings of this study emphasise that strengthening the legal framework must be accompanied by context-specific implementation strategies to ensure that occupational health protection for informal workers can be delivered more effectively and sustainably.